2004
DOI: 10.1007/s00595-003-2726-9
|View full text |Cite
|
Sign up to set email alerts
|

Left Thyroid Lobe Hemiagenesis with Hyperthyroidism: Report of a Case

Abstract: Thyroidal hemiagenesis resulting from the failure of development of one thyroidal bud to develop accounts for fewer than 0.1% of thyroidal disorders necessitating surgery. This rare congenital anomaly usually occurs on the left side. Any nonfunctional lobe detected by scintigraphy needs to be evaluated further by ultrasonography, because thyroid hemiagenesis is associated with varying degrees of morbidity when it coexists with other anomalies requiring surgical intervention. We report the case of a 38-year-old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Most common of these being hyperthyroidism, associated with thyroid hemiagenesis. However, as seen in our patient, hemithyroid agenesis can also be associated with a hypothyroid or euthyroid states as well [3,4,6]. A recent large cohort case study revealed that patients with thyroid hemiagenesis were more likely to develop thyroid pathology in the remnant thyroid lobe, including functional, morphological, and autoimmune diseases with Hashimoto's thyroiditis being the most common of the pathologies encountered [7].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Most common of these being hyperthyroidism, associated with thyroid hemiagenesis. However, as seen in our patient, hemithyroid agenesis can also be associated with a hypothyroid or euthyroid states as well [3,4,6]. A recent large cohort case study revealed that patients with thyroid hemiagenesis were more likely to develop thyroid pathology in the remnant thyroid lobe, including functional, morphological, and autoimmune diseases with Hashimoto's thyroiditis being the most common of the pathologies encountered [7].…”
Section: Discussionsupporting
confidence: 56%
“…Hemithyroid agenesis is a rare congenital anomaly of the thyroid and been has found to be three time more common in females as compared to males [4]. In 80% cases the left thyroid lobe is absent and in about 50% of patients with left hemithyroid agenesis will also have an absent thyroid isthmus [5].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, many cases of hemiagenesis discovered upon workup of the hyperthyroidism. However as noted earlier and in our patient, hemithyroid agenesis can be associated with a hypothyroid or euthyroid state as well [2,4,6]. A recent large cohort case study revealed that patients with thyroid hemiagenesis were more likely to develop thyroid pathology.…”
Section: Discussionmentioning
confidence: 55%
“…Hemithyroid agenesis a rare congenital anomaly of thyroid has found to be three time more common in females as compared to males [4]. In 80% the left thyroid lobe is absent and in about 50% of patients with left hemithyroid agenesis will also have an absent thyroid isthmus [5].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence is higher in women (3:1, as was also in the present case), which may indicate a possible gender association (2). Hyperthyroidism has been reported to be the most common clinical presentation leading to an incidental diagnosis of the hemiagenesis (1113). Our case presented with multi-nodular goiter which has be reported as the second most common association.…”
Section: Discussionmentioning
confidence: 99%